2014
DOI: 10.7567/apex.7.071004
|View full text |Cite
|
Sign up to set email alerts
|

Self-terminating growth in hexagonal boron nitride by metal organic chemical vapor deposition

Abstract: In this work, we demonstrate the growth of atomically smooth few-layer hexagonal boron nitride (h-BN) on sapphire substrates by metal organic chemical vapor deposition using triethylboron (TEB) and NH3 as precursors. Changing the V/III ratio in a certain temperature and pressure range was found to change the growth mode from random 3D nucleation to self-terminating growth. Infrared reflectance and Raman spectroscopy were used to identify the h-BN phase of these films. Atomic force microscopy measurements confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…Development of a self-terminating CVD/MOCVD process on insulating substrates similar to what has been done on single-crystal transition metals in UHV [6,7] is desirable for producing few-to mono-layer films with uniform thickness over large areas. In our previous report on growth of BN by MOCVD [8], we showed that atomically smooth few-layer thick BN can be achieved under a self-terminating growth mode at high V/III ratios.…”
Section: Introductionmentioning
confidence: 88%
“…Development of a self-terminating CVD/MOCVD process on insulating substrates similar to what has been done on single-crystal transition metals in UHV [6,7] is desirable for producing few-to mono-layer films with uniform thickness over large areas. In our previous report on growth of BN by MOCVD [8], we showed that atomically smooth few-layer thick BN can be achieved under a self-terminating growth mode at high V/III ratios.…”
Section: Introductionmentioning
confidence: 88%
“…The TO ⊥ peak position for the freestanding h-BN film is the closest to that for exfoliated h-BN nanosheets 25 and CVD grown h-BN thin films. 26,27 The softening effect has been reported on Ni(111), on which h-BN forms a commensurate layer, resulting in a π−d orbital hybridization that downshifts the TO ⊥ phonon significantly. 16 Although the TO ⊥ peak positions of h-BN film on Ru(0001) and Pt foil are slightly softened compared with bulk h-BN, the amount of softening is very small, suggesting that the overall h-BN-substrate interaction is not very strong, as both metals form incommensurate structures with h-BN.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 97%
“…6(a) due to the self-terminating effect. 18,19 Despite similar thickness of the films, however, there is a significant change in optical absorption spectra, as shown in Fig. 6(b).…”
mentioning
confidence: 93%
“…1(c). The both h-BN films consist of only a few atomic layers which is due to self-terminating effect occurring at low pressure and high V/III ratio growth conditions, 18,19 but the films have a different saturated thickness depending on the carrier gas. It is also experimentally observed that thickness of the sample is no longer increasing when the total pulse cycle number is increased further (not shown here).…”
mentioning
confidence: 99%
See 1 more Smart Citation